The design and preliminary application of a training model for manual therapy for lymphedema (一种手法淋巴引流培训教具装置的设计与应用) - WANG Yuan (王媛); WANG Pei (王蓓); WANG Fengmei (王凤美); DING Yong (丁勇); XIA Shun (夏舜) (中西医结合护理, 2021)
In order to meet the growing demand of lymphotherapists, training and patients, guidance, a specific model was designed for training manual lymphatic drainage therapy. The design and application effect of this model is described and discussed in this study. The model can easily let the operator know whether the manipulation is accurate, whether the operation pressure is stable and whether the drainage effect is satisfactory for further adjustments. The design is very close to the clinical practice and the operation of the model is simple and convenient. Preliminary application of this training model showed good effect in better understanding and mastering manipulation technique both in therapists and the patients, as well as their family members. (本研究针对当前淋巴治疗师培训及患者指导上的缺陷, 设计了一种淋巴水肿手法淋巴引流培训教具装置, 并对设计思路及使用效果加以分析。通过使用手法淋巴引流培训教具装置进行操作练习, 可以直观的感受到操作手法的准确性、操作压力的稳定性及引流操作的效果, 增强治疗师的培训成效, 提高患者或者家属掌握的可控性, 进而提升淋巴水肿治疗师培训及患者指导的应用效果。该手法淋巴引流培训教具装置操作简单方便, 应用效果显著。)